PENGARUH NILAI PREMI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMILIHAN ASURANSI JASINDO OTO (Studi Kasus Pada PT. Asuransi Jasindo Semarang) - Silitonga, Sunriati Grace; Suryoko, Sri; Saryadi, Saryadi (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2013)
Auto insurance is an insurance product Jasindo motor vehicle owned by PT. Insurance Jasindo Semarang (Persero). Several factors will determine the selection decision is the value of insurance premiums and quality of service. Premium value or price has two main roles in the decision making process of the buyer, that is the allocation role and information role. Good quality services will give a good image or reputation in the eyes of consumers so that consumers will be attracted to choose services. This study aimed to determine the effect of premium value and service quality toward the selection decision of insurance. Type of research is explanatory research. With a sample of 78 respondents who use jasindo oto insurance through non probability sampling technique which is purposive sampling. The analysis technique uses test validity, reliability testing, simple linear regression, multiple linear regression, t test and F test with SPSS tools 15. The results showed an effect of premium value of 85,1% against the decision of the selection jasindo auto insurance. Affect the quality of service is 90,8% against the decision of the selection of auto insurance jasindo. Simultaneously, the influence rate of premium value and service quality is at 92.3%. Based on data analysis, it can be inferred partially and simultaneously that the premium value and service quality significantly influence selection decision and have a very strong level of closeness relationship. Suggested, the company needs to conduct training for employees to improve their skills regarding information presentation techniques.